Paleoambiente y paleontología de la Formación Andapaico (Paleozoico superior, Precordillera Central, Argentina) - Correa, Gustavo Alejandro (2012)
A sedimentological, paleontological and paleoenvironmental study of the Andapaico Formation is presented (southern sector of the Paganzo Basin, San Juan). This unit overlies with an angular unconformity the Punta Negra Formation, and has a thickness of 430 m of siliciclastic sediments, that include deposits formed predominantly in nearshore environments. Lower shoreface (facies association I), anastomosed rivers and floodplain (II), high sinuosity rivers (III), beach (IV), eolian system (V), barrier island (VI) and lagoon (VII) deposits were identified. Facies association I (lower part of the unit) and VII (upper part) and their associated palynoflora assign them to the early Cisuralian (I) and late Cisuralian-early Guadalupian (VII, Lueckisporites-Weylandites Biozone). From the facies I association a fossil plant assemblage was obtained that allows it to be referred to the Ferugliocladus Superzone of the early Permian of the Tepuel-Genoa Basin, which reinforces the hypothesis of this age for the lower part of the Andapaico Formation.